Hubungan Mekanisme Koping Dengan Depresi Pada Mahasiswa Tingkat Akhir Sekolah Tinggi Ilmu Kesehatan Indonesia Jaya - Jumain Jumain; Wahyu; Agustinus Talindong; Parmi; Saiful Ambodale; Lexy Kareba; Sudirman; Subardin AB (Universitas Widya Nusantara, 2025)
Background: Final year students are vulnerable to academic and psychological stress that can impact mental health, especially depression. Coping mechanisms used by students play an important role in determining an individual's ability to deal with stress. Objective: This study aims to determine the relationship between coping mechanisms and depression in final year students at the Indonesian Jaya College of Health Sciences. Method: This study used a quantitative design with a cross-sectional approach. The sample size was 40 final year students selected using a total sampling technique. Data were collected using a coping mechanism and depression questionnaire, then analyzed univariately and bivariately. The statistical test used was the Chi-square test with a significance level of α = 0.05. Results: The results of the univariate analysis showed that most respondents had adaptive coping mechanisms (27 respondents (67.5%) and did not experience depression (34 respondents (85.0%). The bivariate analysis showed that all respondents with adaptive coping mechanisms did not experience depression (100.0%), while some respondents with maladaptive coping mechanisms experienced depression. The Chi-square test results obtained a p-value of 0.000 (p < 0.05), which indicates a significant relationship between coping mechanisms and depression in final year students. Conclusion: There is a significant relationship between coping mechanisms and depression in final year students at the Indonesia Jaya College of Health Sciences. Adaptive coping mechanisms act as a protective factor against depression.